EXPLORATION OF THE METABOLITES AND STRUCTURAL ANATOMY OF SEED COAT DORMANCY IN BLACK GRAM VBN-8 USING GAS CHROMATOGRAPHY MASS SPECTROMETRY (GC-MS) AND SCANNING ELECTRON MICROSCOPY (SEM) ANALYSIS - S POZHILARASI; MENAKA C; YUVARAJA A; SENTHIL K; DJANAGUIRAMAN M; RAJA K; VANITHA C (Journal of Animal and Plant Sciences, 2025)
Hard seed is a physical dormancy due to hard seed coat particularly present in leguminous crop. This type of dormancy is caused by impermeability of seed coat which prevents water imbibition and thus inhibits timely and uniform germination. It is one of the undesirable physiological traits that makes the seed unfit for immediate crop production after harvest. Thus, investigating metabolites and structural anatomy is an integrative approach to understanding the mechanisms that control seed coat dormancy. Seed coat characteristics are critical for seed germination, vigour, and longevity, with hard seed coats often leading to dormancy due to impermeability. Understanding dormancy mechanisms can help crop production become more adaptable to changing climate conditions, ensuring food security and sustained agricultural output in the face of environmental problems. This study was conducted at NPRC, Vamban for VBN 8 raised in field conditions and the Department of Seed Science & Technology, TNAU, Coimbatore for laboratory work to investigate the biochemical metabolites and cuticle and palisade layer structure of black gram seed coats using GC‒MS & SEM. Freshly harvested seeds were soaked in water for this study. After the imbibition process, the seeds were categorized into two types: hard and non-hard. GC-MS analysis identified key metabolites contributing to hardseededness, including fatty acids, phenolic compounds, and alcohols. Among the fatty acids, octadecanoic acid was found in higher concentrations (27.48) in hard seeds compared to non-hard seeds. The phenolic compound 3-tert-butyl-4-hydroxyanisole (10.76) and the alcohol hexadecanol (1.29) were also recorded at higher levels in hard seeds compared to non-hard seeds. SEM analysis revealed that hard seeds have a thicker cuticle layer, a denser palisade layer and a rougher seed surface compared to non-hard seeds, contributing to their greater impermeability and dormancy. In contrast, non-hard seeds have a thinner, more permeable seed coat with larger pores, which facilitates faster water absorption and germination. These structural and biochemical characteristics result in the hydrophobicity and dormancy associated with hard seeds. The finding can guide the appropriate breeding program and designing suitable agronomic strategy is aimed at reducing the dormancy under variable environmental conditions to distinguish hard and non-hard seeds in black gram. Subsequently ensures high seed rate replacement and crop productivity in black gram. This innovative approach offers substantial advancements in understanding and improving seed quality parameters.
Keywords: Seed coat-imposed dormancy; Hard seed; Non-hard seed; Key metabolites; Cuticle and palisade layer